Non-authentic space as a tourist product – an example of Lower Silesia - Belof, Magdalena; Główczyńska, Aleksandra (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2016)
The paper deals with the problem of spatial and landscape transformations caused by the development and globalization of tourism, including, in particular, the formation of the so- called “non-authentic spaces”, ie. Newly created tourist spaces, not connected with local and regional natural and cultural assets. The authors discuss the relationship between this phenomena with the issue of commercialization of tourist space, as well as the change of the paradigm of tourism from the so-called. 3s (sea, Sun, sand) to 3e (entertainment, excitement, education), which caused an avalanche of investments in the sphere of entertainment and recreation both in Poland and in the world. Selected examples of non-authentic spaces from Lower Silesia are presented and discussed.